2007
DOI: 10.1002/jbm.a.31425
|View full text |Cite
|
Sign up to set email alerts
|

Deformation behavior, corrosion resistance, and cytotoxicity of Ni‐free Zr‐based bulk metallic glasses

Abstract: Two Ni-free bulk metallic glasses (BMGs) of Zr(60)Nb(5)Cu(22.5)Pd(5)Al(7.5) and Zr(60)Nb(5)Cu(20)Fe(5)Al(10) were successfully prepared by arc-melting and copper mold casting. The thermal stability and crystallization were studied using differential scanning calorimetry. It demonstrates that the two BMGs exhibit very good glass forming ability with a wide supercooled liquid region. A multi-step process of crystallization with a preferential formation of quasicrystals occurred in both BMGs under continuous heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 32 publications
(30 reference statements)
4
32
0
Order By: Relevance
“…The observed biocompatibility can possibly be explained by the formation of highly corrosion-resistant and biocompatible oxides such as Zr oxide in a physiological environment. [9] The resulting stable oxide layer acts as a barrier in blocking the diffusion of toxic metal ions and therefore improving the overall cytotoxicity. [23] It could also be due to the good corrosion resistant property exhibited by BMGs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed biocompatibility can possibly be explained by the formation of highly corrosion-resistant and biocompatible oxides such as Zr oxide in a physiological environment. [9] The resulting stable oxide layer acts as a barrier in blocking the diffusion of toxic metal ions and therefore improving the overall cytotoxicity. [23] It could also be due to the good corrosion resistant property exhibited by BMGs.…”
Section: Resultsmentioning
confidence: 99%
“…Research has been reported on the general cytotoxicity of Zr-based BMGs using fibroblast cells. [8,9] The objective of this study was to investigate the application specific osteoblast cell growth and activity on a zirconium (Zr)-based BMG substrate, to compare the results to the most commonly used titanium alloy of Ti-6Al-4V, and to determine whether this BMG material deserves further detailed biological investigations and mechanistic studies. Specifically, the osteoblast cell attachment, proliferation, differentiation, and morphology were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the oxide itself shows bio-inertness and low solubility. 12,50,51 Mo is an essential trace element and the 150-500 lg/day level was estimated as adequate and safe for adults. 52 Based on previous cytotoxicity and biocompatibility studies of metals, Mo was classified as a low cytotoxic and safe element for living body.…”
Section: Biocompatibility Of Zr-mo Alloys and Their Promises As Medicmentioning
confidence: 99%
“…As a result, nickel and beryllium free Zr-and Ti-based BMGs were considered. [10][11][12][13][14] However, these alloy systems have relatively lower glass-forming ability when compared with the multicomponent BMGs such as the ZrTiCuNiBe BMG series. Ni or Be elements are often necessary to enhance the glass formability as their use can introduce large atomic size difference when compared with other elements such as Zr.…”
Section: Introductionmentioning
confidence: 98%